Propriedades físicas e mecânicas da madeira de Angelim SP obtidas de árvores provenientes de regiões distintas do país - Teixeira, Julia Naves (Universidade Federal de São Carlos, 2021)
In Brazil, the use of wood in civil construction structures is regulated by the technical standard NBR-7190 "Wood Structures Project", of the Brazilian Association of Technical Standards (ABNT, 1997), which does not establish the possibility of influence of extraction regions in the wood properties. The aim of this research was to investigate the influence of different regions of wood extraction from Angelim Pedra on its physical and mechanical properties. In this research, it was also evaluated, with the help of ANOVA of the regression models, the possibility of being able to estimate the strength properties and some physical properties of the wood as a function of the apparent density. It was concluded that lots from all regions had a high equivalence index; the Bonfim region showed full equivalence and Mucajaí and Claudia showed an equivalence index equal to 93% in both analyses. As for the estimation of properties by bulk density, it was observed that it was impossible to estimate properties by regression models. The characteristic value relationships, used in the simplified characterization of the wood found in this research, were superior to the values ​​established in the Brazilian Standard ABNT NBR 7190; demonstrates that the results obtained in this study can be used, in a new revision of the Standard on the relationships used, for the simplified characterization of wood.
Physical and mechanical properties of madeira de Angelim SP obtained from trees from different regions of the country
Keywords: Madeira; Norma brasileira; Regiões de extração; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS